Effect of cryoprotectant and its level to survivability of drake semen - Kusumaningrum D.A; P Situmorang; A.R Setioko; T Sugiarti; E Triwulanningsih; R.G Sianturi (Jurnal Ilmu Ternak dan Veteriner, 2002)
This study was conducted at Laboratory Reproduction of Physiology, Research Institute of Animal Production. The experiment was factorial design with two kinds of cryoprotectant (DMF and DMA) as the first factor and two levels of them (7 and 9%) as the second factor. This study was invented to determine the effect of cryoprotectant and its level to survivability of drake semen. Sperm was collected from fifteen drakes two times per week using artivicial vagina. Only the best quality of sperm was used in this study. Collected sperm was diluted in medium to get concentration of 400 x 106 per ml. Equilibrated at 50C in mini straw (0.25 ml) for 60 minutes, then kept them up 8 cm above the LN2 for 4 minutes before plunged in LN2. Parameters measured of this study were survability of drake semen after diluted, at 50C and after freezing-thawing at 350C for 30 seconds. Result of this study showed that percentage of motility and percentage of live sperm were significant different (P<0.05) between DMA (33.24 and 42.03) and DMF (25.82 and 34.30). Level of cryoprotectant (7 and 9%) were not significant different. Based on this study, using DMA as cryoprotectan with 7% in medium was better than that of DMF.   Key words: Cryoprotectan, survivability, drake sperm